Optical glass and optical element
A controlled oxide composition in optical glass minimizes Gd2O3 content while achieving high refractive index and low dispersion, addressing cost and performance challenges in optical glass production.
Patent Information
- Application Number
- JP2024111232
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-21
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-31
AI Technical Summary
The high cost of Gd2O3, a component in high refractive index optical glass, necessitates the development of a glass composition with a low Gd2O3 content while maintaining high refractive index and other desirable optical properties.
A specific oxide composition is formulated with controlled ranges of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5, TiO2, and other components to achieve a high refractive index and low dispersion optical glass, minimizing Gd2O3 content.
The solution provides optical glass with a high refractive index and low dispersion, reducing material costs and maintaining glass stability and transparency, suitable for optical elements.
Smart Images

Figure 2025016358000001 
Figure 2025016358000002 
Figure 2025016358000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical glass and an optical element. [Background technology]
[0002] In recent years, optical glasses with high refractive indices have been proposed as materials for optical elements (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-128539 A Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 1 (JP Patent Publication 2002-128539 A), a glass composition that realizes a high refractive index is Gd 2 O 3 A glass composition containing a large amount of Gd has been disclosed (see the examples in JP-A-2002-128539). 2 O 3 Since Gd is an expensive component whose unit price has risen sharply in recent years, it is necessary to use Gd 2 O 3 Glasses with a low content are preferred.
[0005] In view of the above, one aspect of the present invention is to provide a method for producing a Gd 2 O 3 The object of the present invention is to provide an optical glass having a high refractive index with a small content. [Means for solving the problem]
[0006] One aspect of the present invention is as follows. [1] In the glass composition based on oxides expressed in mole percent, SiO 2Content is 0.00% or more and 30.00% or less, B 2 O 3 Content is 30.00% or more and 80.00% or less, La 2 O 3 Content is 8.00% or more and 40.00% or less, Gd 2 O 3 Content is 0.00% or more and 3.00% or less, Y 2 O 3 Content is 2.00% or more and 10.50% or less, ZnO content is 1.00% or more and 20.00% or less, ZrO 2 Content is 0.00% or more and 15.00% or less, Nb 2 O 5 Content is 0.40% or more and 5.00% or less, TiO 2 Content is 0.00% or more and 3.00% or less, SrO content is 0.00% or more and 1.00% or less, and La 2 O 3 , Y 2 O 3 and the total content of ZnO (La 2 O 3 +Y 2 O 3 +ZnO) is 27.40% or more, Optical glass. [2]SiO 2 and B 2 O 3 The total content of (SiO 2 +B 2 O 3 ) is 56.80% or more and 63.44% or less. [3] ZrO 2 and Nb 2 O 5 and the total content (ZrO 2 +Nb 2 O 5 ) is 0.40% or more and 9.80% or less. [4] ZrO2 and Nb 2 O 5 and the total content (ZrO 2 +Nb 2 O 5 ) is 7.93% or more and 9.80% or less. [5] Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 ) is 2.20 or more and 4.15 or less. [6] Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 ) is 2.345 or more and 3.46 or less. [7] La 2 O 3 , Gd 2 O 3 and Y 2 O 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 )) is 2.20 or more and 2.59 or less. [8]Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 +TiO 2 +WO 3 )) is 31.10 or more. [9]Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 +TiO 2 +WO 3 )) is 31.10 or more and 88.50 or less.
[10] Nb 2 O 5 ZnO and Y content 2 O 3 The molar ratio of the total content of ZnO and Y 2 O 3 ) / Nb 2 O 5 ) is 5.00 or more and 18.00 or less.
[11] SiO 2 and B 2 O 3 The total content of (SiO 2 +B 2 O 3 ) is between 56.80% and 63.44% ZrO 2 and Nb 2 O 5 and the total content (ZrO 2 +Nb 2 O 5 ) is between 7.93% and 9.80%; Y 2 O 3 La content 2 O3 Molar ratio of content (La 2 O 3 / Y 2 O 3 ) is between 2.345 and 3.46, La 2 O 3 , Gd 2 O 3 and Y 2 O 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 ) is greater than or equal to 2.20 and less than or equal to 2.59, Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 +TiO 2 +WO 3 )) is greater than or equal to 31.10 and less than or equal to 88.50, and Nb 2 O 5 ZnO and Y content 2 O 3 The molar ratio of the total content of ZnO and Y 2 O 3 ) / Nb 2 O 5 ) is 5.00 or more and 18.00 or less.
[12] An optical element comprising the optical glass according to any one of [1] to
[11] . Effect of the Invention
[0007] According to one aspect of the present invention, Gd 2 O 3 It is possible to provide an optical glass having a low content and a high refractive index, and an optical element made of this optical glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Optical glass] In the present invention and this specification, the glass composition of optical glass is expressed as a glass composition based on oxides expressed in mole percent. Here, "glass composition based on oxides" refers to a glass composition obtained by converting the glass raw materials into oxides that exist in the glass after being completely decomposed during melting. In the glass composition expressed in mole percent, the glass composition is expressed on a molar basis (mol%, molar ratio). Hereinafter, for glass compositions expressed in mole percent, "mol%" will also be simply referred to as "%".
[0009] In the present invention and this specification, the content of a component being 0%, 0.0% or 0.00%, or not containing or not introducing, means that the component is substantially not contained, and the content of the component is at or below the impurity level. At or below the impurity level means, for example, less than 0.01%. "0%" can mean, for example, "0.0%" or "0.00%". The content of a certain component being "0% or more", "0.0% or more", or "0.00% or more" means that the component is an optional component.
[0010] The glass composition of the present invention and this specification can be determined by a method such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed for each element using ICP-AES. The analytical values are then converted into oxide notation. The analytical values obtained by ICP-AES may contain a measurement error of, for example, about ±5% of the analytical value. Therefore, the oxide notation values converted from the analytical values may also contain an error of about ±5%.
[0011] In the present invention and this specification, the refractive index refers to the refractive index nd at the d line of helium (wavelength 587.56 nm).
[0012] In the present invention and this specification, the Abbe number νd is used as a value representing a property related to dispersion, and is expressed by the following formula. νd=(nd-1) / (nF-nC) In the above formula, nF is the refractive index at the F line of blue hydrogen (wavelength 486.13 nm), and nC is the refractive index at the C line of red hydrogen (656.27 nm).
[0013] The optical glass (sometimes simply referred to as "glass") will be described in more detail below.
[0014] <Glass composition> SiO 2 The content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. SiO 2 is a glass network component, and when its content is reduced, the viscosity of the glass decreases, and the moldability tends to decrease. 2 The content is preferably 0.50% or more, and more preferably 1.00% or more, 1.50% or more, 2.00% or more, 2.50% or more, 3.00% or more, 3.50% or more, and 4.00% or more in that order. On the other hand, SiO 2When the content is large, the melting property and refractive index of the glass tend to decrease. 2 The content is 30.00% or less, preferably 28.00% or less, and more preferably 26.00% or less, 24.00% or less, and 22.00% or less in that order.
[0015] B 2 O 3 is a glass network component and also a component that lowers the melting temperature of glass. 2 O 3 If the content is low, the glass network component becomes insufficient, and the glass stability tends to decrease. 2 O 3 The content is 30.00% or more, preferably 32.00% or more, and more preferably 34.00% or more, 36.00% or more, 38.00% or more, and 40.00% or more in that order. On the other hand, B 2 O 3 The effect of volatilization increases as the content of B increases. Therefore, from the viewpoint of ease of controlling optical properties, 2 O 3 The content is 80.00% or less, preferably 75.00% or less, and more preferably 70.00% or less, 65.00% or less, and 60.00% or less in that order.
[0016] SiO 2 and B 2 O 3 The total content of (SiO 2 +B 2 O 3 ) is preferably 56.80% or more, more preferably 57.00% or more, and further preferably 57.50% or more, 58.00% or more, 58.50% or more, 59.00% or more, and 60.00% or more in that order, from the viewpoint of enhancing the stability of the glass. On the other hand, in order to suppress the decrease in the refractive index of the glass, the total content (SiO 2 +B 2 O 3) is preferably 63.44% or less, more preferably 63.30% or less, and further preferably 63.10% or less, 62.90% or less, 62.70% or less, and 62.60% or less in that order.
[0017] La 2 O 3 La is a component that contributes to a high refractive index and low dispersion of the glass. 2 O 3 The content is 8.00% or more, preferably 9.00% or more, and more preferably 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 16.00% or more, and 17.00% or more in that order. On the other hand, La 2 O 3 If the content is large, the glass tends to become highly dispersed, tends to devitrify, and has a large specific gravity. 2 O 3 The content is 40.00% or less, preferably 35.00% or less, and more preferably 30.00% or less, 25.00% or less, and 21.00% or less in that order.
[0018] Gd 2 O 3 The content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. Gd 2 O 3 The content of Gd is a component that contributes to increasing the refractive index and decreasing the dispersion of the glass. 2 O 3 Since Gd is a component that is expensive and increases the specific gravity, it is preferable to add it to the glass in as small an amount as possible. 2 O 3 The content is 3.00% or less, preferably 2.50% or less, more preferably 2.00% or less, 1.50% or less, 1.00% or less, and 0.50% or less in that order, and most preferably 0.00%.
[0019] Y 2 O 3Y is a component that contributes to increasing the refractive index and decreasing the dispersion of the glass. 2 O 3 The content is 2.00% or more, preferably 2.50% or more, and more preferably 3.00% or more, 3.50% or more, 4.00% or more, 4.50% or more, 5.00% or more, 5.50% or more, and 6.00% or more in that order. On the other hand, Y 2 O 3 If the content is large, the glass tends to become highly dispersed and tends to become devitrified. 2 O 3 The content is 10.50% or less, preferably 10.00% or less, more preferably 9.00% or less, and more preferably 8.00% or less.
[0020] From the viewpoint of suppressing the crystallization of glass, Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 ) is greater than or equal to 2.20 and less than or equal to 4.15. From the viewpoint of suppressing the crystallization of glass, Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 ) is preferably 2.20 or more, more preferably 2.30 or more, 2.31 or more, 2.32 or more, 2.33 or more, 2.34 or more, or 2.345 or more. In addition, from the viewpoint of suppressing crystallization of glass, the molar ratio (La 2 O 3 / Y 2 O 3 ) is preferably 4.15 or less, and more preferably 4.00 or less, 3.80 or less, 3.60 or less, 3.46 or less, 3.40 or less, and 3.20 or less in that order.
[0021] La 2 O3 , Gd 2 O 3 and Y 2 O 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 )) is preferably 2.20 or more, and more preferably 2.21 or more, 2.22 or more, 2.23 or more, 2.24 or more, 2.25 or more, 2.26 or more, and 2.27 or more in that order, from the viewpoint of enhancing the stability of the glass. On the other hand, from the viewpoint of suppressing the decrease in the refractive index of the glass, the molar ratio ((SiO 2 +B 2 O 3 ) / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 )) is preferably 2.59 or less, and more preferably 2.57 or less, 2.55 or less, 2.53 or less, 2.51 or less, 2.49 or less, 2.47 or less, and 2.46 or less in that order.
[0022] ZnO is a component that lowers the glass transition temperature Tg. The ZnO content is 1.00% or more, preferably 1.05% or more, and more preferably 1.10% or more, 1.15% or more, 1.20% or more, 1.25% or more, and 1.30% or more in that order. On the other hand, if the ZnO content is high, the glass tends to crystallize and the stability of the glass tends to decrease. From the above viewpoints, the ZnO content is 20.00% or less, preferably 18.00% or less, and more preferably 16.00% or less, 14.00% or less, 12.00% or less, 10.00% or less, 8.00% or less, and 7.00% or less.
[0023] La 2 O3 , Y 2 O 3 and the total content of ZnO (La 2 O 3 +Y 2 O 3 From the viewpoint of low dispersion of the glass, the total content (La +ZnO) is 27.40% or more, preferably 27.50% or more, more preferably 27.60% or more, and even more preferably 27.70% or more. 2 O 3 +Y 2 O 3 +ZnO) can be, for example, 40.00% or less, 39.00% or less, 38.00% or less, 37.00% or less, 36.00% or less, 35.00% or less, 34.00% or less, or 33.00% or less.
[0024] ZrO 2 The content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. 2 is a component that contributes to a high refractive index and low dispersion of glass. 2 The content is preferably 1.00% or more, and more preferably 2.00% or more, 3.00% or more, 4.00% or more, 5.00% or more, and 6.00% or more in that order. On the other hand, ZrO 2 If the content is too high, the meltability of the glass tends to decrease. From the viewpoint of maintaining the meltability of the glass, ZrO 2 The content is 15.00% or less, preferably 14.00% or less, and more preferably 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, and 9.00% or less in that order.
[0025] Nb 2 O 5 From the viewpoints of increasing the refractive index, reducing dispersion, and improving the stability of the glass, the content is 0.40% or more, preferably 0.45% or more, and more preferably 0.50% or more, 0.55% or more, 0.60% or more, 0.65% or more, and 0.70% or more in that order. On the other hand, Nb 2 O 5If the content is large, the meltability of the glass tends to decrease, and the Abbe number νd also tends to decrease. Therefore, from the viewpoint of maintaining the meltability of the glass and reducing dispersion, Nb 2 O 5 The content is 5.00% or less, preferably 4.50% or less, and more preferably 4.00% or less, 3.50% or less, 3.00% or less, 2.50% or less, and 2.00% or less in that order.
[0026] ZrO 2 and Nb 2 O 5 and the total content (ZrO 2 +Nb 2 O 5 ) is preferably 0.40% or more, from the viewpoint of achieving a high refractive index and low dispersion of the glass, and is more preferably 0.50% or more, 1.00% or more, 1.50% or more, 2.00% or more, 2.50% or more, 3.00% or more, 3.50% or more, 4.00% or more, 4.50% or more, 5.00% or more, 5.50% or more, 6.00% or more, 6.50% or more, 7.00% or more, 7.50% or more, 7.70% or more, 7.80% or more, 7.90% or more, and 7.93% or more, in that order. On the other hand, from the viewpoint of suppressing the crystallization of glass, the total content (ZrO 2 +Nb 2 O 5 ) is preferably 9.80% or less, more preferably 9.70% or less, and more preferably 9.60% or less, 9.50% or less, 9.40% or less, and 9.30% or less in that order.
[0027] Nb 2 O 5 ZnO and Y content 2 O 3 The molar ratio of the total content of ZnO and Y 2 O 3 ) / Nb 2 O 5 With respect to the molar ratio (ZnO+Y), when the molar ratio is small, the Abbe number νd tends to be large, and when the molar ratio is large, the Abbe number νd tends to be small. From the viewpoint of controlling the Abbe number νd within a range desirable for optical element materials, the molar ratio ((ZnO+Y 2O 3 ) / Nb 2 O 5 ) is preferably 5.00 or more, and more preferably 5.20 or more, 5.40 or more, 5.60 or more, 5.80 or more, and 6.00 or more in that order. From the above viewpoint, the molar ratio ((ZnO+Y 2 O 3 ) / Nb 2 O 5 ) is preferably 18.00 or less, more preferably 17.00 or less, and even more preferably 16.00 or less.
[0028] TiO 2 The content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. TiO 2 is a component that contributes to increasing the refractive index and decreasing the dispersion of glass. However, it is a component that reduces the transmittance of glass. From the viewpoint of suppressing the decrease in the transmittance of glass, TiO 2 The content is 3.00% or less, preferably 2.00% or less, more preferably 1.00% or less, even more preferably 0.50% or less, and most preferably 0.00%.
[0029] Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 +TiO 2 +WO 3 With regard to the molar ratio of (SiO), as the value of this molar ratio increases, the glass tends to have a high dispersion, and as the value of this molar ratio decreases, the glass tends to have a low dispersion. From the viewpoint of controlling the Abbe number νd within a range desirable for optical element materials, 2 +B 2 O 3 ) / (Nb 2 O5 +TiO 2 +WO 3 )) is preferably 31.10 or more, more preferably 32.00 or more, 33.00 or more, 34.00 or more, 35.00 or more, and 36.00 or more in that order. Molar ratio ((SiO 2 +B 2 O 3 ) / (Nb 2 O 5 +TiO 2 +WO 3 )) can be, for example, 120.00 or less, 110.00 or less, 100.00 or less, 98.00 or less, 96.00 or less, 94.00 or less, 92.00 or less, 90.00 or less, 89.00 or less, or 88.50 or less.
[0030] In the above glass, WO 3 and Bi 2 O 3 The content of each of is 0.00% or more, and can be 0.00% or more than 0.00%. WO 3 and Bi 2 O 3 WO is a component that contributes to imparting high refractive index and low dispersion to the glass. By keeping the content of each component at 2.00% or less, it is possible to suppress a decrease in the transmittance of the glass for ultraviolet to visible light (particularly wavelengths of 500 nm or less). From this point of view, WO 3 and Bi 2 O 3 The content of each of these is preferably 2.00% or less, more preferably 1.50% or less, 1.00% or less, and 0.50% or less in that order, and most preferably 0.00%.
[0031] SrO is a component that contributes to a high refractive index and low dispersion of the glass. The SrO content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. As the SrO content increases, the glass tends to become more susceptible to devitrification. Therefore, from the viewpoint of maintaining glass stability, the SrO content is 1.00% or less, preferably 0.90% or less, and more preferably 0.80% or less, 0.70% or less, 0.60% or less, and 0.50% or less in that order.
[0032] Each of the contents of MgO, CaO and BaO is 0.00% or more and can be 0.00% or more than 0.00%. From the viewpoint of suppressing devitrification of the glass and realizing desired optical properties, each of the contents of MgO, CaO and BaO is preferably 5.00% or less, more preferably 4.00% or less, and further preferably 3.00% or less, 2.00% or less, and 1.00% or less in that order.
[0033] Li 2 The O content is 0.00% or more, and may be 0.00% or more. From the viewpoints of further improving the thermal stability of the glass, suppressing a decrease in the glass transition temperature (thereby improving machinability), and improving chemical durability and weather resistance, Li 2 The O content is preferably 5.00% or less, more preferably 4.00% or less, 3.00% or less, and further preferably 2.00% or less in that order.
[0034] Na 2 OK 2 O, Rb 2 O and Cs 2 The content of each of O is 0.00% or more, and can be 0.00% or more than 0.00%. 2 OK 2 O, Rb 2 O and Cs 2 Although O has the function of improving the meltability of glass, when the content of these elements increases, the thermal stability, chemical durability, weather resistance and machinability of the glass tend to decrease. 2 OK 2 O, Rb 2 O and Cs 2The respective contents of O are preferably 5.00% or less, more preferably 4.00% or less, 3.00% or less, and 2.00% or less in that order.
[0035] As for other glass components, Al 2 O 3 The content can be 0.00%, 0.00% or more, or more than 0.00%. 2 O 3 The content can be, for example, 5.00% or less, 4.00% or less, 3.00% or less, or 2.00% or less.
[0036] Regarding other glass components, considering the environmental impact, As 2 O 3 The content is preferably 0.10% or less, more preferably 0.01% or less, and most preferably 0.00%. In consideration of the environmental impact, the PbO content is preferably 1.00% or less, more preferably 0.50% or less, and more preferably 0.10% or less, and most preferably 0.00%.
[0037] Ta 2 O 5 From the viewpoint of reducing the cost of glass, Ta 2 O 5 The content is preferably 2.00% or less, more preferably 1.50% or less, 1.00% or less, and 0.50% or less in that order, and is most preferably 0.00%.
[0038] Sb 2 O 3 Sb is a component that can be added as a clarifier. Adding a small amount can suppress the decrease in light transmittance caused by the inclusion of impurities such as Fe. 2 O 3 The more Sb is added, the more coloring of the glass tends to increase. 2 O 3The amount of Sb added is preferably 0.00% or more and 0.10% or less, more preferably 0.00% or more and 0.08% or less, and even more preferably 0.00% or more and 0.05% or less, in terms of the external proportion. 2 O 3 The content is Sb 2 O 3 Sb expressed as mass% when the total content of glass components other than Sb is 100 mass% 2 O 3 This means the content of.
[0039] SnO 2 Sn can also be added as a fining agent, but if it is added in an amount exceeding 1.00% by weight, the glass will become colored, and when the glass is heated, softened, and reshaped by press molding, Sn will become the starting point for crystal nucleation, causing a tendency for devitrification. 2 The amount of SnO added is preferably 0.00% or more and 1.00% or less, more preferably 0.00% or more and 0.50% or less, and particularly preferably none is added. 2 The content is SnO 2 SnO expressed as mass% when the total content of glass components other than SnO is 100 mass%. 2 This means the content of.
[0040] <Glass properties> (Refractive index nd) The glass can be a high refractive index glass by having the above glass composition. From the viewpoint of usefulness as a material for optical elements, the refractive index nd of the glass is preferably 1.7860 or more, more preferably 1.7861 or more, and further preferably 1.7862 or more, 1.7863 or more, 1.7864 or more, 1.7865 or more, 1.7866 or more, 1.7867 or more, 1.7868 or more, 1.7869 or more, 1.7870 or more, 1.7871 or more, 1.7872 or more, 1.7873 or more, 1.7874 or more, and 1.7875 or more in this order. Furthermore, from the viewpoint of usefulness as a material for optical elements, the refractive index nd of the above glass is preferably 1.7935 or less, more preferably 1.7934 or less, and more preferably 1.7933 or less, 1.7932 or less, 1.7931 or less, 1.7930 or less, 1.7929 or less, 1.7928 or less, 1.7927 or less, 1.7926 or less, 1.7925 or less, 1.7924 or less, 1.7923 or less, and 1.7922 or less, in that order.
[0041] (Abbe number νd) The above glass can exhibit low dispersion by having the above glass composition. From the viewpoint of usefulness as a material for optical elements, the Abbe number vd of the above glass is preferably 48.50 or less, more preferably 48.45 or less, and further preferably 48.40 or less, 48.35 or less, 48.30 or less, 48.25 or less, 48.20 or less, 48.15 or less, 48.10 or less, and 48.05 or less in that order. From the viewpoint of usefulness as a material for optical elements, the Abbe number vd of the above-mentioned glass is preferably 46.50 or more, more preferably 46.60 or more, and further preferably 46.70 or more, 46.80 or more, 46.90 or more, 47.00 or more, 47.10 or more, 47.20 or more, and 47.30 or more, in that order.
[0042] (specific gravity) The refractive power of the optical elements that make up an optical system is determined by the refractive index of the glass that makes up the optical element and the curvature of the optical functional surface of the optical element (the surface through which the light rays to be controlled enter and exit). If you try to increase the curvature of the optical functional surface, the thickness of the optical element also increases. As a result, the optical element becomes heavier. In contrast, if glass with a high refractive index is used, it is possible to obtain a large refractive power without increasing the curvature of the optical functional surface. From the above, if the refractive index can be increased while suppressing an increase in the specific gravity of the glass, it will be possible to reduce the weight of an optical element having a certain refractive power. From the above viewpoints, the specific gravity of the glass is preferably 5.00 or less, more preferably 4.95 or less, and more preferably 4.90 or less, 4.85 or less, 4.80 or less, 4.75 or less, 4.70 or less, 4.65 or less, 4.60 or less, and 4.55 or less in that order. Since a lower specific gravity is more preferable from the viewpoint of reducing the weight of the optical element, the lower limit of the specific gravity of the glass is not particularly limited. In one embodiment, the specific gravity of the glass can be, for example, 4.00 or more, 4.05 or more, 4.10 or more, 4.15 or more, 4.20 or more, or 4.25 or more. In the present invention and this specification, the "specific gravity" is a value measured by the Archimedes method.
[0043] (Coloring degree λ 5 , λ 80 ) The light transmittance of the glass, specifically, the suppression of the shift of the light absorption edge on the short wavelength side to longer wavelengths, is the coloring degree λ 5 and λ 80 The coloring degree λ can be evaluated by one or more of the following: 5 λ represents the wavelength at which the spectral transmittance (including surface reflection loss) of glass with a thickness of 10±0.1 mm is 5% from the ultraviolet region to the visible region. 80 is λ 5 The wavelengths at which the spectral transmittance measured by the method described above is 80% are shown in the table below. 5 and λ 80 is a value measured in the wavelength range of 250 to 700 nm. The spectral transmittance T (%) of glass in the present invention and this specification is calculated by dividing the intensity of light incident perpendicularly on one of two optically polished parallel planes of a glass sample by the intensity of light I in The intensity of the light that passes through the glass sample and exits from the other side is I out When T(%)=I out / I in ×100 It is expressed as: Coloring degree λ 5 and λ 80According to this method, the absorption edge on the short wavelength side of the spectral transmittance can be quantitatively evaluated. For example, when lenses are bonded together with an ultraviolet-curable adhesive to produce a cemented lens, the adhesive is cured by irradiating it with ultraviolet light through an optical element. From the viewpoint of efficiently curing the ultraviolet-curable adhesive, it is preferable that the absorption edge on the short wavelength side of the spectral transmittance is in a short wavelength range. As an index for quantitatively evaluating the absorption edge on the short wavelength side, the coloring degree λ 5 and λ 80 One or more of the following may be used. The glass preferably has a λ of 330 nm or less. 5 It can be shown that λ 5 is more preferable in the following order: 329 nm or less, 328 nm or less, 327 nm or less, 326 nm or less, 325 nm or less, 324 nm or less, 323 nm or less, 322 nm or less, 321 nm or less, 320 nm or less, 319 nm or less, 318 nm or less, and 317 nm or less. λ 5 is more preferable as the wavelength is shorter, and the lower limit is not particularly limited. 5 can be 300 nm or more, 301 nm or more, 302 nm or more, 303 nm or more, or 304 nm or more. The glass preferably has a λ of 410 nm or less. 80 It can be shown that λ 80 is more preferably 409 nm or less, 408 nm or less, 407 nm or less, 406 nm or less, 405 nm or less, 404 nm or less, 403 nm or less, 402 nm or less, 401 nm or less, and 400 nm or less, in that order. 80 is more preferable as the wavelength is shorter, and the lower limit is not particularly limited. 80 can be 380 nm or greater, 381 nm or greater, 382 nm or greater, 383 nm or greater, 384 nm or greater, or 385 nm or greater.
[0044] (glass transition temperature Tg) From the viewpoint of machinability (more specifically, from the viewpoint of resistance to breakage during mechanical processing of the glass, such as cutting, milling, grinding, polishing, etc.), the glass transition temperature Tg of the above glass is preferably 640°C or higher, and more preferably 645°C or higher, 650°C or higher, 655°C or higher, and 660°C or higher, in that order. On the other hand, from the viewpoint of reducing the burden on the annealing furnace and the molding die, the glass transition temperature Tg of the above glass is preferably 750° C. or less, more preferably 745° C. or less, 740° C. or less, 735° C. or less, 730° C. or less, and 725° C. or less in that order. The glass transition temperature Tg is determined by a differential scanning calorimeter at a heating rate of 10° C. / min.
[0045] <Method of manufacturing optical glass> The optical glass can be obtained by weighing, preparing and thoroughly mixing raw materials such as oxides, carbonates, sulfates, nitrates and hydroxides so as to obtain the desired glass composition, heating and melting the mixture in a melting vessel, degassing and stirring the mixture to produce a homogeneous, bubble-free molten glass, and then molding the glass. Specifically, the glass can be produced by using a known melting method.
[0046] [Glass material for press molding, optical element blanks, and their manufacturing methods] Another aspect of the present invention is a glass material for press molding comprising the optical glass; an optical element blank made of the optical glass; Regarding.
[0047] According to another aspect of the present invention, a method for producing a glass material for press molding, comprising a step of molding the optical glass into a glass material for press molding; a method for producing an optical element blank, comprising a step of press-molding the glass material for optical glass press molding using a press mold to produce an optical element blank; A method for producing an optical element blank, comprising the step of forming the optical glass into an optical element blank; will also be provided.
[0048] An optical element blank is an optical element base material that approximates the shape of a target optical element and has polishing margins (surface layers to be removed by polishing) and, if necessary, grinding margins (surface layers to be removed by grinding) added to the shape of the optical element. The optical element is finished by grinding and polishing the surface of the optical element blank. In one embodiment, the optical element blank can be produced by a method (called a direct press method) in which a molten glass obtained by melting an appropriate amount of the above glass is press-molded. In another embodiment, the optical element blank can also be produced by solidifying a molten glass obtained by melting an appropriate amount of the above glass.
[0049] In another embodiment, a glass material for press molding is prepared, and the prepared glass material for press molding is press molded to produce an optical element blank.
[0050] The press molding of the glass material for press molding can be carried out by a known method in which the glass material for press molding in a heated and softened state is pressed in a press mold. Both heating and press molding can be carried out in the atmosphere. By annealing after press molding to reduce distortion inside the glass, a homogeneous optical element blank can be obtained.
[0051] Glass materials for press molding include not only those called glass gobs for press molding, which are used for press molding as they are to produce optical element blanks, but also those that are mechanically processed such as by cutting, grinding, polishing, etc., and are used for press molding via glass gobs for press molding. Cutting methods include a method in which a groove is formed in the portion of the surface of the glass plate to be cut by a method called scribing, and local pressure is applied to the grooved portion from the back side of the surface on which the groove is formed, thereby breaking the glass plate at the grooved portion, and a method in which the glass plate is cut by a cutting blade. Grinding and polishing methods include barrel polishing, etc.
[0052] The glass material for press molding can be produced, for example, by casting molten glass into a mold to form a glass plate, and cutting this glass plate into a plurality of glass pieces. Alternatively, a suitable amount of molten glass can be molded to produce a glass gob for press molding. An optical element blank can also be produced by reheating, softening, and press-molding the glass gob for press molding. The method of producing an optical element blank by reheating, softening, and press-molding glass is called a reheat press method, as opposed to a direct press method.
[0053] [Optical element and its manufacturing method] Another aspect of the present invention is An optical element made of the above optical glass Regarding.
[0054] The optical element is produced using the optical glass. In the optical element, the glass surface may be coated with one or more layers of coating, such as a multilayer film including an anti-reflection film.
[0055] According to another aspect of the present invention, A method for producing an optical element, comprising the step of producing an optical element by grinding and / or polishing the optical element blank described above; will also be provided.
[0056] In the manufacturing method of the optical element, the mechanical processing such as grinding and polishing can be performed by applying a known method, and the surface of the optical element after processing can be sufficiently cleaned and dried to obtain an optical element with high internal quality and surface quality. In this way, an optical element made of the optical glass can be obtained. Examples of optical elements include various lenses such as spherical lenses, aspherical lenses, and microlenses, and prisms.
[0057] In addition, the optical element made of the optical glass is also suitable as a lens constituting a cemented optical element. Examples of cemented optical elements include a cemented lens formed by cementing lenses together, and a lens and a prism. For example, a cemented optical element can be produced by precisely processing the cemented surfaces of two optical elements to be cemented (for example, by spherical polishing) so that the shapes are inverted, applying an ultraviolet-curing adhesive used for bonding the cemented lens, bonding them together, and then irradiating ultraviolet light through the lens to cure the adhesive. In order to produce a cemented optical element in this way, the optical glass is preferable. A plurality of optical elements to be cemented are each produced using a plurality of types of glass having different Abbe numbers νd, and cemented together to produce an element suitable for correcting chromatic aberration. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.
[0059] [Example 1] <No.1~156> The raw materials for introducing each component were the corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc., and the raw materials were weighed and thoroughly mixed to obtain the glass composition (unit: mol%) shown in the table below. The mixed raw materials were placed in a platinum crucible and heated and melted for two hours in a furnace set at 1350° C. The molten glass was stirred to homogenize it, then poured into a preheated mold and allowed to cool to near the glass transition temperature. It was then immediately placed in an annealing furnace and held at about the glass transition temperature for about 30 minutes, after which it was slowly cooled at a rate of −30° C. / hour for four hours, and then allowed to cool to room temperature in the furnace to obtain the optical glasses No. 1 to 156 shown in the table below. Sb shown in the table below 2 O 3 The content is the exclusive content (unit: mass %). The physical properties of the optical glass thus obtained are shown in the following table. The physical properties of the optical glasses were measured by the methods described below.
[0060] <Evaluation of physical properties of optical glass> (1) Refractive index nd Abbe number νd The refractive index nd and Abbe number vd of the obtained glass were measured by the refractive index measurement method specified by the Japan Optical Glass Industry Association.
[0061] (2) Glass transition temperature Tg The glass was thoroughly crushed in a mortar and used as a sample. A platinum cell was used as a sample container, and the glass transition temperature Tg was measured at a heating rate of 10°C / min using a Rigaku differential scanning calorimeter (DSC8271).
[0062] (3) Specific gravity Specific gravity was measured by Archimedes' method.
[0063] (4) Coloring degree λ 5 , λ 80 A glass sample having a thickness of 10±0.1 mm and two optically polished flat surfaces facing each other was used to measure the spectral transmittance T (%) using a spectrophotometer. The wavelength (nm) at which T becomes 5% is defined as λ 5 Let λ be the wavelength (nm) at which T is 80%. 80 It was decided.
[0064] [Table 1-1]
[0065] [Table 1-2]
[0066] [Table 1-3]
[0067] [Table 1-4]
[0068]
Table 1-5
[0069]
Table 1-6
[0070]
Table 1-7
[0071]
Table 1-8
[0072]
Table 1-9
[0073]
Table 1-10
[0074]
Table 1-11
[0075]
Table 1-12
[0076]
Table 1-13
[0077]
Table 1-14
[0078] [Table 1-15]
[0079] [Table 1-16]
[0080] [Example 2] A glass gob for press molding was prepared using the various glasses obtained in Example 1. The glass gob was heated and softened in the atmosphere, and press molded in a press mold to prepare a lens blank (optical element blank). The prepared lens blank was removed from the press mold, annealed, and machined, including polishing, to prepare a spherical lens made of the various glasses prepared in Example 1.
[0081] [Example 3] A desired amount of the molten glass produced in Example 1 was press molded in a press mold to produce a lens blank (optical element blank). The produced lens blank was removed from the press mold, annealed, and subjected to mechanical processing including polishing to produce a spherical lens made of the various glasses produced in Example 1.
[0082] [Example 4] The molten glass produced in Example 1 was solidified to produce a glass lump (optical element blank), which was then annealed and machined, including polishing, to produce spherical lenses made of the various glasses produced in Example 1.
[0083] [Example 5] The spherical lenses produced in Examples 2 to 4 were bonded to spherical lenses made of other types of glass to produce cemented lenses. The cemented surfaces of the spherical lenses produced in Examples 2 to 4 were convex, and the cemented surfaces of the spherical lenses made of other types of glass were concave. The above two cemented surfaces were produced so that the absolute values of the radii of curvature were equal to each other. An ultraviolet-curing adhesive for bonding optical elements was applied to the cemented surfaces, and the two lenses were bonded together with their cemented surfaces facing each other. Thereafter, ultraviolet light was irradiated onto the adhesive applied to the cemented surfaces through the spherical lenses produced in Examples 2 to 4 to solidify the adhesive. A cemented lens was produced in the manner described above. The cemented lens had a sufficiently high bonding strength and exhibited a sufficient level of optical performance.
[0084] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by subjecting the above-mentioned exemplary glass compositions to compositional adjustments as described in the specification, an optical glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.
Claims
1. In the glass composition based on oxides expressed in mole percent, SiO 2 The content is 0.00% or more and 30.00% or less, B 2 O 3 The content is 30.00% or more and 80.00% or less, La 2 O 3 The content is 8.00% or more and 40.00% or less, G.D. 2 O 3 The content is 0.00% or more and 3.00% or less, Y 2 O 3 The content is 2.00% or more and 10.50% or less, ZnO content is 1.00% or more and 20.00% or less, ZrO 2 The content is 0.00% or more and 15.00% or less, Nb 2 O 5 The content is 0.40% or more and 5.00% or less, TiO 2 The content is 0.00% or more and 3.00% or less, The SrO content is 0.00% or more and 1.00% or less, and La 2 O 3 , Y 2 O 3 and the total content of ZnO (La 2 O 3 +Y 2 O 3 +ZnO) is 27.40% or more, Optical glass.
2. SiO 2 and B 2 O 3 The total content of 2 +B 2 O 3 2. The optical glass according to claim 1, wherein the ratio of Cr to H is 56.80% or more and 63.44% or less.
3. ZrO 2 and Nb 2 O 5 The total content of ZrO 2 +Nb 2 O 5 2. The optical glass according to claim 1, wherein the content of Cd is 0.40% or more and 9.80% or less.
4. ZrO 2 and Nb 2 O 5 The total content of ZrO 2 +Nb 2 O 5 2. The optical glass according to claim 1, wherein the content of Cd is 7.93% or more and 9.80% or less.
5. Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 2. The optical glass according to claim 1, wherein the refractive index is 2.20 or greater and 4.15 or less.
6. Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 2. The optical glass according to claim 1, wherein the refractive index is 2.345 or greater and 3.46 or less.
7. La 2 O 3 , Gd 2 O 3 and Y 2 O 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 2. The optical glass according to claim 1, wherein n is 2.20 or greater and 2.59 or less.
8. Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 + TiO 2 +W.O. 3 2. The optical glass according to claim 1 , wherein the refractive index is 31.10 or greater.
9. Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 + TiO 2 +W.O. 3 2. The optical glass according to claim 1 , wherein the refractive index is 31.10 or greater and 88.50 or less.
10. Nb 2 O 5 ZnO and Y content 2 O 3 The molar ratio of the total content of ZnO+Y 2 O 3 ) / Nb 2 O 5 2. The optical glass according to claim 1, wherein the refractive index is 5.00 or greater and 18.00 or less.
11. SiO 2 and B 2 O 3 The total content of 2 +B 2 O 3 ) is 56.80% or more and 63.44% or less, ZrO 2 and Nb 2 O 5 The total content of ZrO 2 +Nb 2 O 5 ) is 7.93% or more and 9.80% or less, Y 2 O 3 La content 2 O 3 Molar ratio of content (La 2 O 3 / Y 2 O 3 ) is equal to or greater than 2.345 and equal to or less than 3.46; La 2 O 3 , Gd 2 O 3 and Y 2 O 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 ) is equal to or greater than 2.20 and equal to or less than 2.59; Nb 2 O 5 , TiO 2 and W.O. 3 SiO relative to the total content 2 and B 2 O 3 The molar ratio of the total content of (SiO 2 +B 2 O 3 ) / (Nb 2 O 5 + TiO 2 +W.O. 3 ) is equal to or greater than 31.10 and equal to or less than 88.50, and Nb 2 O 5 ZnO and Y content 2 O 3 The molar ratio of the total content of ZnO+Y 2 O 3 ) / Nb 2 O 5 2. The optical glass according to claim 1, wherein the refractive index is 5.00 or greater and 18.00 or less.
12. An optical element comprising the optical glass according to any one of claims 1 to 11.
Citation Information
Patent Citations
Low fluorescent optical glass
JP2002128539A